Correction to: Data Analysis and Optimization for Engineering and Computing Problems - Vasant, Pandian; Litvinchev, Igor; Marmolejo Saucedo, José Antonio; Rodríguez Aguilar, Román; Martínez Ríos, Félix Orlando (My University, 2020)
This book was inadvertently published without updating the following (or with the following error) © Springer Nature Switzerland AG 2020